SISTEM PENDUKUNG KEPUTUSAN RUMAH TANGGA MISKIN MENGGUNAKAN METODE WEIGHTED PRODUCT - Ira Zulfa (STEKOM PRESS, 2020)
Information technology concerning the use of computers in a government service is needed to facilitate a job in an agency. One of them is in the Community Empowerment and Village Government Agency, Central Aceh Regency, where data management for poor households is still using the manual method, the data that is processed can be lost, damaged or infected by a virus, besides that the data is also not managed properly. good and when data is needed, the data will be difficult to find due to the large number of files piling up. With a decision support system using the web, it is hoped that it can help ease the burden on employees who manage recipients of aid for poor families which will be implemented at the BPMPK Office, Central Aceh Regency.